F-box protein FBXL19–mediated ubiquitination and degradation of the receptor for IL-33 limits pulmonary inflammation - Zhao, Jing (2012)
The ST2L receptor for interleukin 33 (IL-33) mediates pulmonary inflammation and immune system–related disorders, such as asthma and rheumatoid arthritis. At present, very little is known about the molecular regulation of ST2L expression. Here we found that FBXL19, an ‘orphan’ member of the Skp1–Cullin–F-box family of E3 ubiquitin ligases, selectively bound to ST2L to mediate its polyubiquitination and elimination in the proteasome. Degradation of ST2L involved phosphorylation of ST2L at Ser442 catalyzed by the kinase GSK3β. Overexpression of FBXL19 abrogated the proapoptotic and inflammatory effects of IL-33 and lessened the severity of lung injury in mouse models of pneumonia. Our results suggest that modulation of the IL-33–ST2L axis by ubiquitin ligases might serve as a unique strategy for lessening pulmonary inflammation.